2014
DOI: 10.1158/1078-0432.ccr-14-0635
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor-Derived Prostaglandin-E2 Blocks the Induction of Myeloid-Derived Suppressor Cells and Recovers Natural Killer Cell Activity

Abstract: Purpose: Increased frequencies of myeloid-derived suppressor cells (MDSC) correlate with poor prognosis in patients with cancers. Tumor-derived prostaglandin-E2 (PGE2) plays an important role in inducing MDSCs. However, the detailed mechanisms of this induction remain unknown. To develop targeted therapies for MDSCs, we sought to investigate the molecular basis of PGE2-regulated accumulation of MDSCs and their functional consequence on natural killer (NK) cell activity.Experimental Design: The effects of PGE2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
202
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 234 publications
(208 citation statements)
references
References 46 publications
6
202
0
Order By: Relevance
“…These data are concordant with pre-clinical results that showed that MDSCs mediate potent inhibition of conventional NK cells. [28, 29] In addition, increased numbers of MDSC has been detected in patients with diffuse large B cell lymphoma at diagnosis and correlated with worse outcomes. [30, 31] Furthermore tumor infiltrating MDSC have been recognized to recruit Treg cells and be permissive of further tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…These data are concordant with pre-clinical results that showed that MDSCs mediate potent inhibition of conventional NK cells. [28, 29] In addition, increased numbers of MDSC has been detected in patients with diffuse large B cell lymphoma at diagnosis and correlated with worse outcomes. [30, 31] Furthermore tumor infiltrating MDSC have been recognized to recruit Treg cells and be permissive of further tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…27 Platelets can also release growth factors, such as prostaglandin E, vascular endothelial growth factor, and transforming growth factor that disrupt the function of natural killer cells and stimulate the growth of cancer cells. 27,28 Absolute or relative lymphopenia is another important component of a high platelet-to-lymphocyte ratio in patients with NSCLC. The results from a previous study indicated that patients with low lymphocyte nadirs undergoing radiotherapy have lower rates of survival than patients whose lymphocyte levels are higher.…”
Section: Discussionmentioning
confidence: 99%
“…16 Fluorescently labeled cells were acquired in a BD LSRII flow cytometer and analyzed by FlowJo software (TreeStar; see supplemental Methods).…”
Section: Flow Cytometrymentioning
confidence: 99%